Evasão escolar na EJA: contextos e possíveis fatores de exclusão em uma escola da rede municipal de São Leopoldo - Pereira, Lílian de Oliveira (Universidade do Vale do Rio dos Sinos, 2022)
There is an increasing need for young people and adults to guarantee the right to schooling, especially for those who are already in the world of work and who, possibly, return to school in search of more dignity and citizenship. Therefore, despite the social inequalities imposed by contemporary society, there are still those who seek better living conditions, which result in social emancipation, through education. The phenomenon of school dropout deserves to be studied with responsibility, as its consequences can directly affect the professional, social and economic spheres, not only of the dropout student, but also, indirectly, in the community to which they belong. In this way, when the student drops out of school, he also impacts his community's view of the importance of education. In this sense, this research aims to analyze the contexts and factors that contribute to the dropout of EJA students in a school in the Municipal Network of São Leopoldo - RS. The investigated school offers face-to-face classes in Basic Education for Early Childhood Education, Elementary School I, Elementary School II in the morning and afternoon shifts and Youth and Adult Education - EJA in the evening shift. Regarding the methodology, this study used content analysis (BARDIN, 1995) and as data collection techniques interviews and questionnaires. As a result, relevant data were obtained to understand the profile of EJA students and their socioeconomic contexts, as well as data related to the profile of teachers who work in EJA and their pedagogical practices to work with this audience and the management's view of the pedagogical proposal in light of the reality of EJA subjects. From the analyses, it is possible to affirm that dropout in the school space is a problem that is related, among other factors, to family, economic, social and learning contexts of students enrolled in EJA, overcoming a logic of causality or a single factor, and whose complexity needs to be considered in the elaboration of public policies related to the sport.
Keywords: Evasão; Exclusão; Abandono; EJA; Evasion; Exclusion; Abandonment; ACCNPQ::Ciências Humanas::Educação